2019
DOI: 10.3390/en12142650
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Optimization of Offshore Wind Turbines Based on an Opportunistic Maintenance Strategy

Abstract: Owing to the late development of offshore wind power in China, operational data and maintenance experience are relatively scarce. Due to the harsh environmental conditions, a reliability analysis based on limited sample fault data has been regarded as an effective way to investigate maintenance optimization for offshore wind farms. The chief aim of the present work is to develop an effective strategy to reduce the maintenance costs of offshore wind turbines in consideration of their accessibility. The three-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…By grouping maintenance activities of different component, the maintenance cost can be minimized. Xie et al [44] developed an effective opportunistic maintenance strategy to reduce the maintenance costs of offshore wind turbines in consideration of their accessibility. Atashgar and Abdollahzadeh [3] formulated a joint redundancy and imperfect block opportunistic maintenance optimization model for wind farms, and minimizing maintenance costs is one of the objectives of the proposed model.…”
Section: Comparison Analysismentioning
confidence: 99%
“…By grouping maintenance activities of different component, the maintenance cost can be minimized. Xie et al [44] developed an effective opportunistic maintenance strategy to reduce the maintenance costs of offshore wind turbines in consideration of their accessibility. Atashgar and Abdollahzadeh [3] formulated a joint redundancy and imperfect block opportunistic maintenance optimization model for wind farms, and minimizing maintenance costs is one of the objectives of the proposed model.…”
Section: Comparison Analysismentioning
confidence: 99%
“…The findings show the effect that different maintenance costs have on the economic benefits of an opportunistic maintenance strategy. Xie et al [26] established an efficient strategy in view of accessibility for offshore wind turbines to decrease maintenance costs. A failure rate based on minimal data has been estimated using the Weibull distribution with a three-parameter process approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the aspect of TBM, Xie et al 28 developed the system degradation model based on the three-parameter Weibull distribution. The outcomes demonstrated that the failure rate short-term prediction of the three-parameter Weibull model was superior to the two-parameter Weibull model when the fault data were limited, improving the cost savings to 10%.…”
Section: Case Studymentioning
confidence: 99%